1994
DOI: 10.1002/jor.1100120215
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin in the tendon‐synovial complex: Quantitation In vivo and In vitro by elisa and relative mRNA levels by polymerase chain reaction and northern blot

Abstract: An enzyme-linked immunosorbent assay was used to quantitate fibronectin (Fn) levels in the outer synovia (epitenon) and internal fibrous portion (endotenon) of chicken flexor tendon and sheath. Primary cell cultures from these tissues and their secretions also were assayed for Fn levels. The polymerase chain reaction (PCR) was used to determine relative steady-state levels of Fn mRNA in primary cultures of synovial and internal fibroblasts from chicken tendon, and Northern blot analysis was performed to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…The tendons in group B appeared macroscopically normal but had a significant increase in fibroiiectin content compared with group A, but not compared with the controls, which may be due to the low number of controls. In this study, as well as in other studies [1, 3,6,16], fibronectin was also shown to be present in normal endotenon. Before fibronectin possibly could serve as a marker for early tendon damage further investigations are necessary.…”
Section: B Tillcinder Rt Ul I Journui Of' Orthilpuedic Rrsrurch 19 supporting
confidence: 89%
“…The tendons in group B appeared macroscopically normal but had a significant increase in fibroiiectin content compared with group A, but not compared with the controls, which may be due to the low number of controls. In this study, as well as in other studies [1, 3,6,16], fibronectin was also shown to be present in normal endotenon. Before fibronectin possibly could serve as a marker for early tendon damage further investigations are necessary.…”
Section: B Tillcinder Rt Ul I Journui Of' Orthilpuedic Rrsrurch 19 supporting
confidence: 89%
“…Using tendon internal fibroblasts (TIFs) isolated from nearby collagen fibrils in avian flexor hallucis longus tendon, they found TIFs responded differently to applied strain than cells procured from surface paratenon and epitenon, involving time-dependent changes to the cytoskeleton. 48,[58][59][60][61][62][63][64] Groups then used patterned surfaces or fibrous scaffolds (ie, 2.5D environment) to study the effects of surface geometry, organization, and mechanical loading on cell behavior (Figure 3). 58,[65][66][67][68][69][70] While these advancements are important to our understanding of tendon cell biology, the threedimensional (3D) organization of native tendon naturally led to the development of 3D bioreactors to better model in vivo conditions.…”
Section: Two-dimensional Bioreactorsmentioning
confidence: 99%
“…Two‐dimensional (2D) bioreactors to study cellular response to mechanical loading have evolved rapidly since the mid‐1980s, when Banes et al 57,58 helped lay the foundation for the tendon mechanobiology field. Using tendon internal fibroblasts (TIFs) isolated from nearby collagen fibrils in avian flexor hallucis longus tendon, they found TIFs responded differently to applied strain than cells procured from surface paratenon and epitenon, involving time‐dependent changes to the cytoskeleton 48,58‐64 . Groups then used patterned surfaces or fibrous scaffolds (ie, 2.5D environment) to study the effects of surface geometry, organization, and mechanical loading on cell behavior (Figure 3).…”
Section: The History Of Tendon and Ligament Bioreactorsmentioning
confidence: 99%
“…This matrix promotes collagen organization [ 161. In uninjured tendons, fibronectin is found in the epitenon but to a lower degree deeper within the tendon [3,6]. Amiel et al [l] were able to detect fibronectin in the patellar tendon, which has no sheath covering.…”
Section: Introductionmentioning
confidence: 99%